Relationship Between Nutritional Intake and Infectional Diseases with Nutritional Status of Children In The Working Area of Tenggaba Health Center - Dendo, Marninto Evi; Talahatu, Anna Henny; riwu, Rut Rosina (Timorese Journal of Public Health, 2023)
Nutritional status is a condition caused by a balance between nutrient intake from food and the nutritional needs needed for body metabolism. Nutritional status is influenced by two main factors, namely nutritional intake and infectious diseases. In SBD Regency in 2019, there were 100 malnourished toddlers and 348 undernourished. Tenggaba Health Center is one of the community health centers with 33 undernourished toddlers and 77 undernourished toddlers. The purpose of this study was to analyze the relationship between expenditure, the number of family members, knowledge of maternal nutrition, nutritional intake, and infectious diseases with nutritional status of toddlers in the Tenggaba Health Center. The type of research used is quantitative research with a cross-sectional study design with a sample size of 90 toddlers. The sampling method used is simple random sampling. The data obtained were analyzed chi-square test with a significance level of α=0,05. The results showed that the results of the chi-square test for the amount of expenditure (p=0.006), number of family members (p=0,019), and knowledge of maternal nutrition (p=0,000) which means there is a relationship between the amount of expenditure, number of family members and knowledge of nutrition, mothers with the nutritional intake of toddlers. While the results of the chi-square test for nutritional intake of children under five (p=0,000) and infectious diseases (p=0,010) means that there is a significant relationship between nutritional intake of children under five and infectious diseases with nutritional status of children under five.